The Effect of Working Capital Turnover and Inventory Turnover on Profitability in Food and Beverage Companies Listed on the Indonesia Stock Exchange (IDX) - Dian Purnama Sari; Sri Mintarti (FEB Universitas Mulawarman, 2026)
This study aims to determine the effect of working capital turnover and inventory turnover on profitability in food and beverage companies listed on the Indonesia Stock Exchange (IDX). This study uses a purposive sampling method, data obtained from 20 food and beverage companies on the Indonesia Stock Exchange that meet the criteria with a 5-year research (2020-2024). The type of data used is quantitative data and the data source used is the company's financial statements. This study uses an analysis tool, namely SPSS Software Version 26. The results of this study show that the turnover of working capital has an influence on profitability in food and beverage companies listed on the IDX. Meanwhile, inventory turnover does not have a significant effect on profitability in food and beverage companies listed on the IDX